2010
DOI: 10.1002/ijc.25451
|View full text |Cite|
|
Sign up to set email alerts
|

A tritherapy combination of a fusion protein vaccine with immune‐modulating doses of sequential chemotherapies in an optimized regimen completely eradicates large tumors in mice

Abstract: Tumor-induced immunosuppression plays a critical role in both impeding tumor-specific immune responses and limiting the effects of cancer immunotherapy. Analyses of regulatory cells recruited during the growth of the E7-expressing tumor, TC-1, revealed a high percentage of regulatory T cells (Tregs) as well as myeloid-derived suppressor cells (MDSCs) in spleens and tumors. In this study, we proposed that treatment with immune-modulating doses of cyclophosphamide (CTX) and all-trans retinoic acid (ATRA) would r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…32,41 To compensate, low dose CPA treatment has been combined with drugs that specifically reduce MDSC levels such as gemcitabine or ATRA. [42][43][44] We found that the combination of mCPA plus DPX-R9F did not increase MDSC levels, negating the need for additional drugs. MDSC's are essentially akin to haematopoietic stem/ progenitor cells arrested in development, presumably by the inflammatory cytokine milieu created by the tumor.…”
Section: E953407-10 Volume 3 Issue 8 Oncoimmunologymentioning
confidence: 75%
“…32,41 To compensate, low dose CPA treatment has been combined with drugs that specifically reduce MDSC levels such as gemcitabine or ATRA. [42][43][44] We found that the combination of mCPA plus DPX-R9F did not increase MDSC levels, negating the need for additional drugs. MDSC's are essentially akin to haematopoietic stem/ progenitor cells arrested in development, presumably by the inflammatory cytokine milieu created by the tumor.…”
Section: E953407-10 Volume 3 Issue 8 Oncoimmunologymentioning
confidence: 75%
“…ATRA also has been shown to improve the differentiation of DC in cancer patients [38] and to drive the differentiation of monocytes into DC-like cells [39]. Treatment of tumor-bearing mice with ATRA substantially decreased the number of MDSC in spleens and enhanced the effect of cancer vaccines [21, 2426]. Treatment of patients with renal cell carcinoma showed a substantial reduction in the level of MDSC in peripheral blood [27].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies ATRA showed a direct effect on MDSC by causing apoptosis of PMN-MDSC and differentiating M-MDSC to mature myeloid cells (macrophages and DC) [21–23]. Treatment of tumor-bearing mice with ATRA substantially decreased the presence of MDSC in spleens [21, 2426]. Treatment of patients with renal cell carcinoma showed a substantial reduction in the level of MDSC in peripheral blood [27].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, large tumors could be treated with intense regimens in which cyclophosphamide was followed by vaccination in combination with all trans retinoic acid. The latter is known to reduce MDSC and to improve immunity but also to increase Tregs [51], the effect of which probably was prevented by cyclophosphamide pretreatment as this tritherapy locally reduced MDSC, Tregs, and the secretion of immunosuppressive cytokines [52 ]. Other non-mutually exclusive measures are COX-2 inhibitors or TGFb type I receptor kinase inhibitors that both mediate the generation of a Th1 type of microenvironment resulting in increased local immune cell trafficking allowing vaccines to effectively eradicate large tumors [53,54].…”
Section: Changing the Microenvironmentmentioning
confidence: 99%